Identification of The Level of Pest and Disease Damage at The BPDASHL Indragiri Rokan Nursery, Pekanbaru, Riau - Mardhiansyah, M.; Hamido, Dhanu; Pebriandi, Pebriandi; Irfani, Ewi; Lestari, Ika (Jurnal Biologi Tropis, 2025)
Pests and diseases are recurring issues in the cultivation of forest plant seedlings, as they can reduce seedling quality and lead to economic losses due to seedling mortality. Identifying the types of pests and diseases is crucial for implementing more effective, efficient, and environmentally friendly control measures to maintain seedling quality. The methodology used in this study was a field survey with direct observation of seedlings affected by pests and diseases. Data collected included the types of pests and diseases observed in various seedlings, such as Annona muricata, Albizia saman, Archidendron pauciflorum, Parkia speciosa, Nephelium lappaceum, Pometia pinnata, Persea americana, Durio zibethinus, Garcinia mangostana, and Artocarpus heterophyllus. Observations were conducted over an eight-week period. The damage caused by pests and diseases in the BPDASHL nursery was categorized as relatively mild. Common pests identified included beetles, borers, and mealybugs. Meanwhile, diseases frequently observed were yellowing leaves, sprout collapse, stunted growth, and leaf spot.